2010
DOI: 10.1017/s1742170509990275
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating marketing channel options for small-scale fruit and vegetable producers

Abstract: An analytical framework and ranking system is developed to summarize the primary factors affecting marketing channel performance and to prioritize those channels with the greatest opportunity for success. An application of the model is conducted using case-study evidence from four small-scale diversified vegetable crop producers in Central New York. The relative costs and benefits of alternative wholesale and direct marketing channels are investigated, including how the factors of risk, owner and paid labor, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 3 publications
2
76
0
Order By: Relevance
“…This degree of variability was similar to that found in LeRoux et al (2010), who concluded that accurate farm financial assessments of small-scale farms needed to be done on a per-farm basis versus using more generalized enterprise budgets in order to properly account for the vast differences in sales, labor requirements, and other associated costs. Our data also support the conclusions of Conner and Rangarajan (2009), who noted large differences in the enterprise budgets generated by land-grant university research programs versus budgets based on actual farm data from organic diversified vegetable farms, resulting from the complexity of the operations and the smaller scale of production of each individual crop.…”
Section: Discussionsupporting
confidence: 75%
“…This degree of variability was similar to that found in LeRoux et al (2010), who concluded that accurate farm financial assessments of small-scale farms needed to be done on a per-farm basis versus using more generalized enterprise budgets in order to properly account for the vast differences in sales, labor requirements, and other associated costs. Our data also support the conclusions of Conner and Rangarajan (2009), who noted large differences in the enterprise budgets generated by land-grant university research programs versus budgets based on actual farm data from organic diversified vegetable farms, resulting from the complexity of the operations and the smaller scale of production of each individual crop.…”
Section: Discussionsupporting
confidence: 75%
“…Findings from the USDA Agricultural Management Survey (ARMS) indicate that growers who work off-farm generally have fewer incentives to expand and become more efficient than do small growers who do not participate in alternative, off-farm marketing activities [12]. Time involved in customer relations, travel and delivery, processing and packing, and scheduled harvesting to meet the needs of direct marketing varies across direct-marketing venues, but is particularly extensive for farmers markets and u-pick operations [13].…”
Section: Production and Distribution Limitationsmentioning
confidence: 99%
“…Marketing risks faced by farmers when selling in local markets include price competition from multiple sellers with the same product and local angle, rejection based on quality requirements, inability to meet specifications and logistical requirements, and buyers reneging on contracts [13]. These concerns are not easily managed by the smallest farmers, particularly with differences in specifications and packaging across outlets.…”
Section: Production and Distribution Limitationsmentioning
confidence: 99%
“…Farmers with local food sales tend to use more than one marketing channel for fresh produce (Lawless, Stevenson, Hendrickson, & Cropp, 1999;LeRoux, Schmit, Roth, & Streeter, 2010;Uva, 2002). These farmers may have larger farms, and thus have greater quantities of produce for sale at the farmers market.…”
Section: Effects Of Key Factors On Fuel Use Efficiencymentioning
confidence: 99%